2014
DOI: 10.1039/c4ra06861k
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment with iron pyrite (FeS2) nanoparticles increases the production of spinach

Abstract: Certain nano-materials are known to have plant growth promoting effects, which could find applications in agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 39 publications
9
54
1
Order By: Relevance
“…Previous studies involving iron NPs in the soil matrix after seed germination have reported a dosedependent relationship between the iron NP dosage and iron content within different parts of the plant [10,16,42]. However, when applied as only seed treatment, Srivastava et al found no significant difference in iron content in spinach plant leaves with a different iron pyrite (FeS 2 ) NP dosing [12,43]. Our study also confirms the absence of a significant dose-dependent iron content relationship when applying NPs in a "modified seed presoak" strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies involving iron NPs in the soil matrix after seed germination have reported a dosedependent relationship between the iron NP dosage and iron content within different parts of the plant [10,16,42]. However, when applied as only seed treatment, Srivastava et al found no significant difference in iron content in spinach plant leaves with a different iron pyrite (FeS 2 ) NP dosing [12,43]. Our study also confirms the absence of a significant dose-dependent iron content relationship when applying NPs in a "modified seed presoak" strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Raju et al reported the role of Fe NPs in increasing the radical length and biomass of green gram sprouts during germination [11]. In the study by Srivastava et al, iron pyrite NPs induced a marked increase in the growth of spinach sprouts [12]. Iron pyrite NPs also facilitated a denser network of roots and a significantly (~2.5 times) higher yield in both chili and marigold plants [13].…”
Section: Introductionmentioning
confidence: 98%
“…where n is a factor, which is almost equal to unity for minimum dislocation density. In this work, a typical calculation method has been applied using eqn (1), (6) and 7 32 The doping induces the lattice strain in M x Fe 1Àx S 2 thin films. The lattice parameter for the cubic doped films increases monotonically with doping and consequently induces microstrain in cubic structure of pyrite.…”
Section: Structural Studiesmentioning
confidence: 99%
“…and (7). Lattice constant (a 0 = 0.5420 nm), microstrain (e 0 = 3.031 Â 10 À3 ) and dislocation density (d 0 = 1.075 Â 10 À3 nm À2 ) as calculated by using eqn (1), (6) and 7 (Fig. 3(c)) exhibits three peaks at 288, 324, and 361 cm À1 corresponding to characteristic active modes for oxidized pyrite that might be due to long exposure time for film under high energy laser beam for B1 min during spectrum capture.…”
Section: Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation